An element of the juridical statute of Romanian Principalities in the Ottoman political system (18th century) - Ciobanu, Veniamin (Balcanica Posnaniensia. Acta et studia, 2003)
This study explores a key element of the juridical status of the Romanian Principalities within the Ottoman political system during the 18th century, focusing on the legal and political mechanisms that governed the appointment and recognition of their rulers. While Romanian historiography has extensively examined Romanian-Ottoman relations, many juridical aspects -nparticularly those reflecting the Ottoman perspective – remain insufficiently addressed. The central aim of this research is to analyze the Ottoman conception of sovereignty over the Romanian Principalities and the legal criteria imposed on candidates for princely office. Drawing on a wide array of Ottoman documentary sources – such as firmans, telhis, and official correspondence from the archives – this article offers a nuanced view of how princely legitimacy was constructed, maintained, or revoked in the broader context of Ottoman imperial interests. The findings highlight the dual nature of Ottoman control: while the Sultan exercised formal suzerainty, the complex realities of international conflict (especially the wars with Russia and Austria) and local dynamics often necessitated pragmatic adjustments. Criteria such as loyalty, administrative competence, military utility, and alignment with Ottoman geopolitical strategy shaped the selection of rulers. Moreover, symbolic acts like public ceremonies and the bestowal of caftans – were essential for legitimization, particularly when rulers could not be installed in their capitals due to foreign occupation. The study concludes that the evolving Ottoman requirements for princely eligibility reflected broader imperial strategies to retain control over the Principalities amid declining power. These insights not only clarify the juridical nuances of Ottoman suzerainty but also shed light on the shifting balance between formality and political necessity in late 18th-century Eastern Europe.